Finding the mechanism of esterase D activation by a small molecule. Issue 11 (1st June 2020) - Chen, Xinpeng; Yang, Yuejun; Su, Le; Cui, Xiaoling; Shao, Jing; Liu, Shuyan; Zhao, Baoxiang; Miao, Junying
Graphical abstract: Abstract: People with reduced esterase D (ESD) activity are susceptible to many diseases. However, how to activate ESD is still unknown. To address the question, we identified that 4-chloro-2-(5-phenyl-1-(pyridin-2-yl)-4, 5-dihydro-1H-pyrazol-3-yl) phenol (FPD5) could be a good candidate activator for ESD activity. We found that FPD5 could increase ESD activity in a dose-dependent way. FPD5 bound directly to ESD at Lys180 rather than its ubiquitination site Lys213. Site-directed mutagenesis at the binding site or the ubiquitination site inhibited FPD5 action. FPD5 increased the level of ESD mono-ubiquitination and mutESD K213A completely inhibited this action. Our findings highlighted the activation mechanism of ESD via promoting the mono-ubiquitination of ESD.